The Influence of Accounting Information Systems and Human Resources (HR) Competency of Finance on The Quality of Financial Reports - Deri Kurnia Saputra; Acep Suherman; Tina Kartini (JASa (Jurnal Akuntansi, Audit dan Sistem Informasi Akuntansi), 2021)
Abstract Improper pouring of existing information systems in the company, lack of experience and competence of human resources owned by the company can cause problems in the future for the company. This research was conducted to see the influence of the Accounting Information System and Human Resources Competence (HR) in the Finance Division on the Quality of Financial Statements. The method used is quantitative method. And the type of data used in this study is primary data where primary data is data obtained or obtained directly from sources not through intermediary media. Primary data is specifically collected through questionnaires that already contain questions related to the research being carried out with comparisons of previous research with the results of the realization in the field. During the research process in the field, there were still problems that were found, such as improper financial reporting, inaccurate information systems, and many other problems related to the lack of competence of human resources. And in the process of this research, it produces data that there is a significant influence between the influence of accounting information systems and the competence of human resources (HR) in the finance department on the quality of financial statements.